IMPACT OF ULTRAVIOLET RADIATION ON GERMINATION AND GROWTH PROCESSES OF WHEAT SEEDS - Yu. V. Tertyshnaya; N. S. Levina; O. V. Elizarova (Сельскохозяйственные машины и технологии)
Scientists did not come to a consensus when studying the influence of ultraviolet (UV) radiation on the crop properties and the biometrics of various crops and optimal exposure time and wavelength. The authors studied the influence of UV radiation from a source VL-6.LC with a wavelength of 365 nm for 5 and 30 min for seeds of spring and winter wheat varieties. For seeds of each variety there is the optimum amount of the absorbed radiation energy resulting in the maximum effect. The stimulating influence of UV radiation is not revealed on the seeds of wheat variety Esther having low indicators of viability. The germination of other 4 varieties increased by 1-3 percent. However, biometric indicators of all studied varieties were improved after irradiation. The weight of all varieties wheat seedlings increased after 30 min of irradiation, but especially in case of Moskovskaya 39 and Yubileynaya 100 this indicator reaches up to 20 percent. Five-minute radiation did not caused the similar effect. Height of seedlings depending on the variety is many-valued. After 30 min irradiation this indicator in case of varieties Moskovskaya 39 increased by 30 percent, and of Yubileynaya 100, Dar'ya and Afina it accrues only by 3-5 percen. Root system depend on UV radiation. Root length of all studied varieties except Dar'ya increased up to 60 percent. Therefore the UV radiation does not affect the germination of seeds of the investigated wheat varieties, but significantly changes the seedlings biometrics. It is shown that the action of ultraviolet light is selectively and highly dependent on a variety. The winter wheat Moskovskaya 39 is the most susceptible variety when ultraviolet radiation with a wavelength of 365 nm for 30 min.